Right message, right medium, right time: powering counseling to improve maternal, infant, and young child nutrition in South Asia - Bhanot, Arti; Sethi, Vani; Murira, Zivai; Singh, Konsan Dinachandra; Ghosh, Sebanti; Forissier, Thomas (Frontiers in Nutrition, 2023)
Introduction Quality counseling can positively impact maternal, infant and young child nutrition (MIYCN) behaviors linked to poor nutrition outcomes. Global guidance includes 93 recommendations on MIYCN counseling. Methods A desk review and key informant interviews sought to assess compliance to the recommendations, reach and quality, systemic gaps and opportunities for MIYCN counseling in seven South Asian countries. Ninety-three (93) policies and guidelines, 180 counseling materials and over 50 documents were reviewed; 115 key informant interviews were conducted. Information synthesis captured eight domains. Data from national surveys were analyzed to determine MIYCN counseling reach, quality and association with nutrition behaviors. Results Results showed that national guidelines were inconsistent with global recommendations for seven thematic areas. Coverage of contacts points like antenatal and postnatal care (ANC, PNC) with potential to deliver MIYCN counseling was highly variable. Having at least four ANC contacts was significantly associated with consumption of 100+ iron folic acid tablets in all countries. Rates of early initiation of breastfeeding (18% Pakistan to 90% Sri Lanka) were lower than institutional delivery rates, except for Bangladesh and Sri Lanka. PNC contact within 48 h of birth was positively correlated with exclusive breastfeeding in India, Pakistan and Sri Lanka (OR 1.4, 3.1, 3.2). Health worker contacts and wealth status equally influenced child’s dietary diversity in India. MIYCN services were add-on roles for community-based workers, except in India. Supervision mechanisms exist but were not focused on quality of MIYCN services. Counseling resources were predominantly paper based (>70%), had rural-focused messaging on diets and mainly targeted women. Platforms to engage men were largely missing. Health management information systems included indicators on maternal contact points in all countries but not for children. Assessing funding for MIYCN counseling was challenging as costs were subsumed across several budget line-items. Discussion The research findings can be used to (1) align country guidance with global recommendations, (2) review workforce responsibilities and capacity building with supervision, (3) assess the need for new counseling materials based on coverage of content, service providers and audience, (4) integrate MIYCN counseling indicators in information systems and (5) include MIYCN counseling services with activities and budget in country plans.